Post-Saddam Iraq new realities, old identities, changing patterns - Cohen, Amnon, 1936-; Efrati, Noga (Sussex Academic Press, 2011)
Post-Saddam Iraq comprehensively describes and analyzes the major developments in Iraq, from the US-led invasion up to 2010. The internal political scene - developing along ethnic-sectarian and religious lines (Shi'is and Sunnis, Kurds and Arabs) - is discussed in the context of a reemerging Iraqi national identity. Findings and analyses are based on a systematic study of the Iraqi and Middle Eastern local media, which provides the perspective as to what is taking place in the internal political and social dialogue. Other major developments are also addressed, including women's rights and economic trends. Post-Saddam Iraq offers an important, international dimension to Iraq's post-war development through discussion of: a) the central role played by the Iranian regime and its deep and multi-faceted involvement in the Iraqi internal scene; b) the ambivalent relations with Turkey, which concurrently serves as the main terrestrial channel of trade and economic ties with the world (oil, financial investments); and c) Iraq's marginal position in the affairs of the Arab world. The political and constitutional developments within Iraq are discussed up to the most recent events in late 2010. Nine months after the general elections, a political tug-of-war between the major protagonists has not reached a conclusion, with the intensive involvement of the US behind the scenes attempting to reach an "inclusive" solution. It remains to be seen whether the former centralist policies of the prime minister-to-be will prevail in a state which is gradually disposing of the US military presence, assuming command over its unsolved problems of security and daily life, as well as of its future stability.
Keywords: Postwar reconstruction -- Iraq.; Elections -- Iraq.; Democracy -- Iraq.; Iraq -- Politics and government -- 2003-; Iraq -- Social conditions -- 21st century.; Arab countries -- Foreign relations -- Iraq.; Iraq -- Foreign relations -- Arab countries.; United States -- Foreign relations -- Iraq.; Iraq -- Foreign relations -- United States.; Reconstruction d'après-guerre -- Irak.; Élections -- Irak.; Irak -- Politique et gouvernement -- 2003-; Irak -- Conditions sociales -- 21e siècle.; États arabes -- Relations extérieures -- Irak.; États-Unis -- Relations extérieures -- Irak.; Irak -- Relations extérieures -- États-Unis.; Democracy.; Diplomatic relations.; Elections.; Politics and government.; Postwar reconstruction.; Social conditions.; Arab countries.; Iraq.; United States.; Since 2000